Investment choice and perceived mating intentions regulated by external resource cues and internal fluctuation in blood glucose levels - Rao, Li-Lin; Wang, Xiao-Tian; Li, Shu (Frontiers in Psychology, 2015)
We examined resource allocation priorities in the framework of an updated Maslow hierarchy of fundamental human needs. In Experiment 1, the participants in the food abundance priming condition viewing photos of high-calorie food allocated more money to savings than to spending. However, the participants preferred spending to savings under the condition of mating availability priming with romantic photographs. In Experiment 2, before and after drinking either water or a sugary beverage, fasting participants rated photos of a conversation between a man and a woman. Water drinking lowered the rating scores of mating intentions as well as blood glucose (BG) levels. The sugary drink buffered this decline in sexual perceptivity. Overall, the change in BG levels was positively associated with changes in the ratings of mating intentions but was not associated with other likelihood ratings. These results suggest that both external cues of food and mating resources and internal BG fluctuation regulate the cognitive priority of physiological needs versus mate acquisition and retention.